The Inflation Targeting Framework in Norway - Soikkeli, Jarkko (IMF Working Papers; Working Paper ;, 2002)
Norway adopted an inflation targeting framework in early 2001, thus concluding its gradual but consistent move toward greater exchange rate flexibility. This paper assesses the institutional and technical design of the framework, as well as its potential implications for the practical implementation of monetary policy against the experience from selected industrial countries that had adopted inflation targeting frameworks prior to Norway. Norway's role as a commodity exporter exposed to large terms of trade shocks, and the possible consequences of newly introduced fiscal guidelines are also discussed.